Partially substituting wheat bread with Psyllium husk flour: Nutritional, Textural, and Sensory Characteristics Study - Hiran Karim, Hiran (University of Thi-Qar Journal of agricultural research, 2025)
This study aimed to investigate the impact on bread quality, texture parameters, nutritional qualities, and sensory aspects of partially replacing wheat flour with psyllium husk flour (PHF) at different levels of 5%, 10%, and 15%. The proximate analysis revealed that the amount of moisture, crude fiber and ash content considerably raised with increasing the psyllium husk flour (PHF) to (9.86%, 12.22% and 1.92) respectively, while the amount of protein decreased to 8.38% and fat content decreasing to 0.31%. According to The Farinograph parameters, water absorption (76.5% to 89.77%), development time heightened to (5.53 min), as well as stability decreased from (2.50 min) to (1.20 min) at addition of 15% PHF. Nutritionally, total phenol content (3.31 to 7.92 mg/100g), flavonoids (3.38 to 3.77 mg/100g), antioxidant activity (3.24 to 15.48 μM TE/100g), and minerals content like sodium (Na), calcium (Ca) and iron (Fe) showed significant increasing to (37.73mg/l, 42.88mg/l and 2.78mg/l) correspondingly at the level of 15% psyllium husk flour-enriched bread. Bread weight increased to (143.20gm) as 15% psyllium husk flour added. However, with increasing PHF levels, loaf volume and specific volume decreased from (350.37 to 148.02 cm³) (2.44 to 1.20 cm³/g) respectively, while hardness increased (827 N to 1817 N at 15% PHF) as indicated by texture analysis. Sensory evaluation showed significant declines in taste, texture, and overall acceptability at 15%. Vice versa at PHF ≤ 10%. The results show that a larger substitution level degrades technology. Hence, the PHF 10% content is a good balance between nutritional enrichment and sensory appeal.